GE_GERICHTE C/3110/2013 vom 10. Juni 2016 - GE Cour de justice (2016)
MANDAT; EXÉCUTION DE L'OBLIGATION; DILIGENCE; FAUTE; AUXILIAIRE; DROIT D'ÊTRE ENTENDU; FRAIS JUDICIAIRES; CYBERCRIMINALITÉ | CPC.151; CPC.317.1; CO.402; CO.101.3; CO.44.1; CO.419; CO.422.1